Chronic Post Inguinal Herniorraphy Pain: Prevalence and Risk Factors - Galukande, Moses; Nakalanzi, Aminah; Oling, Michael (Annals of African Surgery, 2016)
Inguinal hernia is a common surgical condition. Whereas complications associated with hernia repair are well documented, chronic postoperative groin pain has received less attention. Objective: To review the frequency and associated risk factors for chronic post herniorrhaphy groin pain at a tertiary urban hospital. Methods: A retrospective descriptive study using data retrieved from patient files and theatre logs was conducted. Only inguinal herniae patients 13 years and above were considered. Pain was self reported at least 3months to 2 years after repair. Results: Eighty nine patient data were analyzed. Mean aged was 40.5years, Male:Female ratio was 6:1. Fifteen (17%) patients reported pain lasting > 3 months. No significant age difference was noted between those with pain and the pain free. All those with chronic pain were male. Conclusion: Inguinodynia was common in this population. Post herniorraphy pain predictive risk factors in this population ought to be investigated.
Keywords: Chronic Pain; Inguinal Hernia Repair; Pain; Surgery